Management and sustainability of ground-mounted solar parks requires consideration of vegetation succession as an omnipresent process - Markus Zaplata (One Ecosystem, 2025)
In addition to the aspects of power generation, land use, aesthetics, nature conservation, and multifunctionality considered so far, there are still overlooked issues in the relatively new topic of solar landscapes. I reveal a connection with a supposedly not equally contemporary theme: ecological succession. Understanding succession provides the background for interrelationships, and explains why, in large solar parks, the occurrence of large operational disruptors, such as trees, cannot be sustainably countered with the usual maintenance measures. Woody plants benefit from the thousands of safe sites amongst the modular panel constructions, and softwoods often avoid being cut due to their flexibility, or grow back from their stumps. Stronger and stronger over time. Instead of relying exclusively on labour-intensive and costly mowing, managers can make use of grazing animals. In this way, simply anticipating the ecological succession process and taking it into account when planning and managing a solar park can boost overall sustainability. The recommendation makes connections with social dimensions and can result in ethically produced meat.